AVALIAÇÃO DA APTIDÃO FÍSICA RELACIONADA À SAÚDE DE CRIANÇAS PRATICANTES DE FUTEBOL (Fiep Bulletin - online, 2023)
Physical fitness is conceptualized by the ability to perform daily activities regularly, and can be divided into physical fitness related to health or performance. Childhood is the ideal period for the development of health-related components of physical fitness. Therefore, the objective of the present study was to evaluate the physical fitness related to the health of children from a soccer school in Piraúba-MG. A descriptive cross-sectional study was carried out. The target population was boys between 8 and 10 years old, members of a soccer school located in a city in the interior of Minas Gerais. Body mass index (BMI), flexibility using the sit-and-reach test, cardiorespiratory endurance using the 6-minute walk/jogging test, and localized muscle endurance using the 1-minute sit-up test (sit up test) were evaluated. ). The results show that these children had BMI and localized muscular resistance classified in the healthy zone. On the other hand, the children's flexibility was classified as fair. Furthermore, the aerobic resistance of the 8-year-olds was good, while the 9- and 10-year-olds were classified as very good. It is concluded that it is of paramount importance that children are encouraged to practice physical exercises. One of the ways for this to happen can be through sports initiation involving the most popular sport in the country, football.